MULTIAGENT SYSTEMS A MODERN APPROACH TO DISTRIBUTED ARTIFICIAL INTELLIGENCE - WEISS GERHARD (CAMBRIDGE THE MIT PRESS, 2001)
The book serves as a comprehensive textbook and reference for graduate-level AI and computer science students. It outlines both theoretical and practical aspects of multiagent systems (MAS)$1 (Bcollections of intelligent entities (software or robotic agents) that communicate and act within a shared environment. Each chapter, written by leading researchers, delves into one major facet of MAS, including agent design, communication, coordination, decision-making, and learning.s
MULTIAGENT SYSTEMS
COMPUTERS
Keywords: COMPUTERS